Measurement of an individual entrepreneur's social capital: a multidimensional model - Fornoni, Mariel (2011)
The aim of this paper is twofold. First of all, we participate in the open discussion on the nature of social capital and we show that the one-dimensional approach is not enough to capture the complex nature of social capital. Second, we present, implement and validate a specific three-dimensional measurement tool that can be used to analyze the role of social capital in further entrepreneurship research. The measurement tool is implemented through a Structural Equation Model, which is estimated and validated from a database including information from 282 Argentinean entrepreneurs who answered a questionnaire specifically designed for this research. Our measurement model considers the dimensions proposed by Koka and Prescott (Strategic Management Journal, 23:795-816, 2002), i.e. relational, resources and structural.